Toxoplasma gondii induced cognitive impairment in rats via dysregulation of dopamine receptors and indoleamine 2,3 dioxygenase - Wana, Mohammed Nasiru; Watanabe, Malaika; Chiroma, Samaila Musa; Unyah, Ngah Zasmy; Basir, Rusliza; Mohd Moklas, Mohamad Aris; Abd Majid, Roslaini; Abdullahi, Sharif Alhassan; Nordin, Shariza (Elsevier, 2023)
Toxoplasma gondii (T. gondii) is a parasite capable of residing in the brain of their host which influences behaviour changes due to alterations in the neurotransmitters. Consequently, dopamine receptors (DRD) and indoleamine 2, 3 dioxygenase (IDO) dysregulation facilitate the progression of behaviour changes in a host as a response to infection. This study tested the effect of neurotransmitter changes as a result of T. gondii infection on rats cognitive impairment. The T. gondii strain of type I, II and III from Malaysia were previously identified by standard procedures. Sporulated oocysts each of type I, II and III were inoculated separately into three groups of Wistar rats (n = 9) respectively. Two separate control groups received either phosphate buffered saline (PBS) or MK-801 (dizocilpine). Behaviour changes were evaluated at nine weeks post infection in a square box, elevated plus maze and gene expression level of DRD and IDO compounds. The study revealed increased fatal feline attraction, reduced anxiety, decreased DRD and increased IDO gene expression in the T. gondii infected groups and MK-801 compared to the PBS control group. In conclusion, T. gondii infection alter the level of neurotransmitters in rat which cause cognitive impairment. This implies that all the T. gondii strain can cause behaviour changes if human were infected.